Mechanical properties of synthetic lightweight coarse aggregate infuse with offshore sand - Mohammad Amirulkhairi, Zubir; Muhammad Nazrin Akmal, Ahmad Zawawi; Mohd Fairuz, Azmi (Penerbit Akademia Baru, 2022)
Alternative replacement for land aggregate is very important for island and coastal region where land aggregate resources is scarce, expensive and even unavailable for construction industries. For country that have limited sources of land aggregate, offshore sand is a potential choice of replacement for their construction industries. This research studied the production and usage of synthetic lightweight coarse aggregate produced using offshore sand (SYLCAG). SYLCAG was produced to replace coarse aggregate that normally use igneous rock for concrete production. It was produced with density of 1300 kg/m3 which is nearly 60% lighter than normal aggregate. This SYLCAG was used as a full replacement for coarse aggregate in concrete which then produced as a concrete with density almost 1900 kg/m3. The produced concrete did not have achieve the design strength of 25 MPa concrete using the standard concrete design. However, it still has the potential to be develop with higher design and later used as structural concrete.